2020
DOI: 10.1007/s10549-020-05816-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of histopathological DCIS features in a large-scale international interrater reliability study

Abstract: Purpose For optimal management of ductal carcinoma in situ (DCIS), reproducible histopathological assessment is essential to distinguish low-risk from high-risk DCIS. Therefore, we analyzed interrater reliability of histopathological DCIS features and assessed their associations with subsequent ipsilateral invasive breast cancer (iIBC) risk. Methods Using a case-cohort design, reliability was assessed in a population-based, nationwide cohort of 2767 women with screen-detected DCIS diagnosed between 1993 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…It is therefore difficult to know if the greater concordance of the three UK pathologists represents the recent focus on consistency of grading of DCIS in the UK; the overall educational and quality assurance mechanisms in place; or simply that they have had the opportunity to work together, discuss problematic cases, and align their approach to DCIS grading. Nevertheless, this supports the use of one international DCIS grading system along with a uniform training programme, as also suggested by other studies [1,[18][19][20]28].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is therefore difficult to know if the greater concordance of the three UK pathologists represents the recent focus on consistency of grading of DCIS in the UK; the overall educational and quality assurance mechanisms in place; or simply that they have had the opportunity to work together, discuss problematic cases, and align their approach to DCIS grading. Nevertheless, this supports the use of one international DCIS grading system along with a uniform training programme, as also suggested by other studies [1,[18][19][20]28].…”
Section: Discussionsupporting
confidence: 89%
“…The proportion of pure DCIS that is ER positive is 68-83% [5,[29][30][31][32], while HER2 positivity ranges from 25 to 35% [5,30,31,33]. IHC scoring for ER and HER2 is reported to have high interobserver agreement between pathologists (intraclass coefficient > 0.8) [5], which is better than the interobserver agreement for grade (presented here and in other studies [18][19][20][21][34][35][36]). Globally, the use of IHC within DCIS is variable; no marker is currently included in the international DCIS pathology minimum data sets, although in some national data sets (e.g.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…Interestingly, Groen et al showed that the median time to invasive recurrence does not significantly differ between low-grade and high-grade DCIS (5,3 versus 5,6 years), nor between BCS alone versus BCS and radiotherapy (5,1 versus 5,9 years). 8 It is clear from the work by Shaaban et al and others that the risk of in situ recurrence is highest in the first five post-operative years, and thereafter, disease-specific survival curves show a changed slope. We believe that these observations, together with the fact that DCIS patients with invasive recurrence have a significantly worse disease-free and overall survival in both the real-world and randomised trial setting, 3,4,9 are sufficiently strong arguments to demand separate reports on the median time to in situ versus invasive recurrence in all future studies on prognostic markers in DCIS.…”
mentioning
confidence: 99%
“…kappa value of 0.55 in the UK Breast External Quality Assurance Scheme [43], several recent studies have shown that there is variability between pathologists, particularly internationally. [9,44] Indeed, whilst most of the literature demonstrates prognostic value to DCIS grade, not all does, which may reflect inter-observer variability as well as the use of different guidelines for definitions of grades. In one recent multi-centre study from the UK, the USA and the Netherlands, an overall kappa for grade of DCIS (low, intermediate or high) was 0.50 (95% CI 0.44-0.56); the pathologists using one set of pathology guidelines from one country had a mildly higher association (kappa = 0.58; 95% CI 0.56-0.61) but it may be that stricter adherence to guidelines is necessary.…”
Section: What Is the Definition Of Low-risk Dcis And How Reproducible Is Diagnosis?mentioning
confidence: 99%